Development of E-Supplement Flipbook Material Amino Acid Compounds from Tampoi Fruit (Baccaurea Macrocarpa) - Hidayat, Niko; Masriani, Masriani; Sasri, Risya; Enawaty, Eny; Erlina, Erlina (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The purpose of this study was to determine the feasibility and response to E-Supplement Amino Acid in Tampoi Fruit (Baccaurea macrocarpa). This research method is research and development (R&D) with the ADDIE model consisting of analysis, design, development, implementation, and evaluation. The data collection technique in this study used measurement techniques with instruments, namely feasibility assessment sheets and response questionnaires. Data analysis used Guttman scale and average calculation. The feasibility of e-supplements was validated by two validators each. The results showed that the E-Supplement of Amino Acids in Tampoi Fruit (Baccaurea macrocarpa) has a feasibility level in the aspects of material, media, and language, which is very feasible (k = 100%). The average percentage of student responses to e-supplements is 90.94% with a very feasible category. So E-Supplement Amino Acids in Tampoi Fruit (Baccaurea macrocarpa) is very feasible to use and get a very good response from students.